Competence Enhancement: Catalyst for Entrepreneurial Self-Efficacy and Entrepreneurial Intention - Liliputra, Angelique Leticia; Setyiawan, Clarissa Febraskynova R.; Liesapali, Karin; Wijaya, Windy Angelica Widya; Purnomo, Windy; Ardyan, Elia (Jurnal Mirai Management, 2025)
Introduction/Main Objectives: This study aims to test cognitive and social competence's influence on entrepreneurial self-efficacy and intention. Background Problems: Making students interested in entrepreneurship is not an easy task. Students require competencies that enhance their entrepreneurial self-efficacy. Novelty: The discourse of this study pertains significantly to the impact of entrepreneurial competence on self-efficacy and entrepreneurial goals. Research Methods: We collected data by issuing online surveys to individuals pursuing bachelor's degrees who owned a company. A total of 167 individuals completed this online quiz. Finding/Results: This study concludes that awareness of personal cognitive competence positively influences self-efficacy, highlighting the importance for the younger generation to understand business and self-related matters to enhance their confidence in business development. Alongside cognitive competency, every individual must possess social competence. In the professional realm, possessing strong social skills positively influences business success and growth. A broad social network is essential to surmount challenges during commercial operations. Conclusion: Entrepreneurial competence (cognitive and social competence) can increase entrepreneurial self-efficacy and entrepreneurial intention.